Bochner-Chen Ideal Submanifolds: Erol Kilic, Mehmet Gulbahar - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we investigateideal invariant submanifolds, ideal anti-invariant submanifolds and ideal CR-submanifolds of Bochner Kaehler manifolds. Moreover, some characterizations related with the holomorphic sectional curvature and the anti-holomorphic sectional curvatureare obtained for Bochner Kaehler manifolds.